Evaluation of cord bilirubin and hemoglobin analysis in predicting pathological jaundice in term babies at risk of ABO incompatibility - Krishnan, Elango; Periasamy, Raja; Sekar, Sathiya Priya (International Journal of Research in Medical Sciences, 2016)
Background: Cord bilirubin and hemoglobin analysis helps not only in predicting the pathological jaundice in ABO incompatibility but also useful for early referral and intervention for better outcome. Aim of this study is to evaluate the cord blood bilirubin and hemoglobin analysis in predicting pathological hyperbilirubinemia in newborn at risk of ABO incompatibility. Methods: In this descriptive study conducted in Government Stanley medical college between January 2016-June 2016, A positive or B positive babies born to O positive mothers with birth weight >2.5 kgs and gestational age >37 weeks were included. A total of 191 babies were studied. Cord bilirubin, reticulocyte count, hemoglobin and fourth day bilirubin were evaluated and data was analysed using Pearson’s Chi square and ANOVA. Results: Out of 191 babies, 25 (13%) did not develop any jaundice, 122 (64%) developed physiological jaundice and 44 (23%) had pathological jaundice. The mean cord bilirubin and cord hemoglobin values of newborn who did not develop jaundice were 1.35mg/dl and 15.3g/dl while the values among pathological jaundice were 3.15mg/dl and 14.97g/dl. Conclusions: Babies with cord bilirubin >1.8mg/dl and hemoglobin <15.1gm/dl are more prone for pathological hyperbilirubinemia.